Factors Influencing the Impact of Fatherlessness on Children’s Mental Health: A Case Study of Working-Class Families - Dwi Putri Lestari; Kamalia (International Journal of Social Sciences and Humanities, 2026)
The phenomenon of fatherlessness in working -class families is one of the problems that affects the psychological and mental health of children due to the low involvement of fathers in parenting. This study aims to analyze the factors influencing fatherlessness and its effects on children's mental health in Saentis Village, Percut Sei Tuan District. The study used a qualitative descriptive case study approach, employing observation techniques, semi-structured interviews, and documentation from three informants selected through purposive sampling. Data analysis was carried out using the Miles and Huberman model as well as thematic analysis. Research results show that structural factors, such as economic limitations, uncertainty about the father's job, divorce, the father's death, and economic demands, influence the emergence of fatherlessness in the family class of workers. Impacted psychological experiences are child covering anxiety (anxiety), feeling insecure, attachment crisis, confusion, identity self, prolonged grief (unresolved grief), and accumulation of disappointment (resentment). According to Erik Erikson's psychosocial theory, the stages differ at each stage of children's development, namely, identity vs. role confusion in adolescents and intimacy vs. isolation in adults in early adulthood. Research shows that this expectation can inform the development of contextualized service guidance and counseling for children who experience fatherlessness.